Metal-tolerant morganella morganii isolates can potentially mediate nickel stress tolerance in Arabidopsis by upregulating antioxidative enzyme activities - Tahir Naqqash; Aeman Aziz; Muhammad Baber; Muhammad Shahid; Muhammad Sajid; Radicetti Emanuele; Abdel-Rhman Z. Gaafar; Mohamed S. Hodhod; Ghulam Haider (Plant Signaling & Behavior)
Plant growth-promoting rhizobacteria (PGPRs) have been utilized to immobilize heavy metals, limiting their translocation in metal contaminated settings. However, studies on the mechanisms and interactions that elucidate how PGPRs mediate Nickel (Ni) tolerance in plants are rare. Thus, in this study we investigated how two pre-characterized heavy metal tolerant isolates of Morganella morganii (ABT9 and ABT3) improve Ni stress tolerance in Arabidopsis while enhancing its growth and yield. Arabidopsis seedlings were grown for five weeks in control/Ni contaminated (control, 1.5 mM and 2.5 mM) potted soil, in the presence or absence of PGPRs. Plant growth characteristics, quantum yield, and antioxidative enzymatic activities were analyzed to assess the influence of PGPRs on plant physiology. Oxidative stress tolerance was quantified by measuring MDA accumulation in Arabidopsis plants. As expected, Ni stress substantially reduced plant growth (shoot and root fresh weight by 53.25% and 58.77%, dry weight by 49.80% and 57.41% and length by 47.16% and 64.63% over control), chlorophyll content and quantum yield (by 40.21% and 54.37% over control). It also increased MDA content by 84.28% at higher (2.5 mM) Ni concentrations. In contrast, inoculation with M. morganii led to significant improvements in leaf chlorophyll, quantum yield, and Arabidopsis biomass production. The mitigation of adverse effects of Ni stress on biomass observed in M. morganii-inoculated plants was attributed to the enhancement of antioxidative enzyme activities compared to Ni-treated plants. This upregulation of the antioxidative defense mechanism mitigated Ni-induced oxidative stress, leading to improved performance of the photosynthetic machinery, which, in turn, enhanced chlorophyll content and quantum yield. Understanding the underlying mechanisms of these tolerance-inducing processes will help to complete the picture of PGPRs-mediated defense signaling. Thus, it suggests that M. morganii PGPRs candidate can potentially be utilized for plant growth promotion by reducing oxidative stress via upregulating antioxidant defense systems in Ni-contaminated soils and reducing Ni metal uptake.